The Idea of a second-order quasi-thought: an objection to the reflexive theory of conscious thought - Vidal, Javier (2005)
The thesis defended in this paper is that theHigher-Order Thought Theory is actually inconsistent. According to the theoryit would be possible to introduce the notion of a second-order quasi-thoughtfrom S. Shoemaker’s notion of a quasi-memory. On the one hand, a secondorderquasi-thought, but not necessarily a quasi-memory, entails an use of ‘I’as subject. On the other hand, Shoemaker conceives the use of ‘I’ as subjectin terms of the notion of an immunity to error through misidentification. Now,as the notion of a quasi-memory as the notion of a second-order quasi-thoughtare liable to allow for the cases of personal and psychological fission where thecausal series between events belonging to one and the same subject is broken,and thus there is not an immunity to error through misidentification. Then, thenotion of a second-order quasi-thought would allow for cases where an use of ‘I’as subject is not immune to error through misidentification!